2008
DOI: 10.1063/1.2815809
|View full text |Cite
|
Sign up to set email alerts
|

Model for reversible nanoparticle assembly in a polymer matrix

Abstract: The clustering of nanoparticles ͑NPs͒ in solutions and polymer melts depends sensitively on the strength and directionality of the NP interactions involved, as well as the molecular geometry and interactions of the dispersing fluids. Since clustering can strongly influence the properties of polymer-NP materials, we aim to better elucidate the mechanism of reversible self-assembly of highly symmetric NPs into clusters under equilibrium conditions. Our results are based on molecular dynamics simulations of icosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 74 publications
0
26
0
Order By: Relevance
“…For low values of the functionality f and polymer size q = 2r g /σ , a grand-canonical approach will result in a bulk solid of NPs. However, the presence of the polymer matrix was shown to provide stabilization to a cluster phase for isotropic particles in the absence of highly directional interactions [16,17]. The origin of this equilibrium cluster formation was found to be a weak, long-ranged repulsion caused by chain connectivity in the polymer matrix.…”
Section: A Simulation Modelmentioning
confidence: 99%
“…For low values of the functionality f and polymer size q = 2r g /σ , a grand-canonical approach will result in a bulk solid of NPs. However, the presence of the polymer matrix was shown to provide stabilization to a cluster phase for isotropic particles in the absence of highly directional interactions [16,17]. The origin of this equilibrium cluster formation was found to be a weak, long-ranged repulsion caused by chain connectivity in the polymer matrix.…”
Section: A Simulation Modelmentioning
confidence: 99%
“…(11) because of the approximation A ≈ r. Equations (10) and (11) imply that L saturates to a constant value at low T, a point extensively discussed below. In living polymer solutions, the magnitude of r (and thus A by analogy) links the string mass at high and low T and also governs the cooperativity of the polymerization transition, 69 as measured by the rate of change of L(T), and the magnitude of the change in the specific heat; similar definitions of cooperativity have been applied to GF liquids. 19,70 In the living polymerization model, the order parameter is the extent of polymerization, defined by the fraction of monomers forming polymeric structures.…”
Section: B Living Polymerization Model Of Stringsmentioning
confidence: 99%
“…In this spirit, we note that independent studies have shown that the stability of block copolymer nanostructures can likewise be enhanced through the incorporation of selective 37 or functional 38 homopolymers that remain mixed within (and do not macrophase-separate from) the copolymer nanostructure. Addition of selective nanoparticles to ordered block copolymers may therefore not only yield novel, spatially-modulated hybrid materials via nanoparticle assembly 39 for a wide variety of growing nanotechnologies, but also provide an alternative physical means by which to promote polymeric nanostructure development. …”
mentioning
confidence: 99%